Rheology, crystallization, and enhanced mechanical properties of uniaxially oriented ethylene–octene copolymer/polyolefin elastomer blends. (14th March 2022) - Long, Ren; Long, Shijun; Zou, Lele; Huang, Zhihan; Huang, Yiwan; Hu, Chuanqun; Li, Dapeng; Li, Xuefeng
Abstract: The application of polyethylene in artificial turf promotes research on the processing and properties of uniaxial extension modified polyethylene materials. The effects of comonomer (octene/butene) structure on the properties of pre-stretched linear low density polyethylene (LLDPE)/polyolefin elastomer (POE) blends are investigated. The melt tensile stress and melt stretch ratio of LLDPE ethylene‒octene copolymer (EOC)/POE reach 4.0 × 10 5 Pa and 12.8, respectively. At the pre-stretching ratio λ = 5, the tensile strength of EOC/POEλ5 reaches 62.5 MPa, the critical length is 5.7 mm, and the strain hardening degree increases. Differential scanning calorimetry, Raman spectroscopy and X-ray diffraction show the crystallinity of EOC/POEλ5 is higher than that of LLDPE ethylene‒butene copolymer (EBC)/POEλ5 . Large short-chain branch length EOC is demonstrated to rebuild the "physical crosslinking point" after pre-stretched, thereby enhancing the interaction between molecular chains in EOC/POEλ5 . This research provides a new clue for the development of artificial turf materials. Graphical abstract: Image 1 Highlights: Pre-stretched ethylene‒octene copolymer/polyolefin elastomer blends are researched. Pre-stretching improves mechanical properties of blends. "Physical crosslinking points" strengthens inter-chain-segmental forces.